2012
DOI: 10.1111/j.1528-1167.2012.03465.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome after cognitive and behavioral regression in nonlesional epilepsy with continuous spike‐waves during slow‐wave sleep

Abstract: Summary Purpose:  To present the long‐term follow‐up of 10 adolescents and young adults with documented cognitive and behavioral regression as children due to nonlesional focal, mainly frontal, epilepsy with continuous spike‐waves during slow wave sleep (CSWS). Methods:  Past medical and electroencephalography (EEG) data were reviewed and neuropsychological tests exploring main cognitive functions were administered. Key Findings:  After a mean duration of follow‐up of 15.6 years (range, 8–23 years), none of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 33 publications
3
40
1
1
Order By: Relevance
“…However, one third of our respondents diagnose CSWS based on EEG assessment alone and two thirds of respondents considered that regression was typical but not required for the diagnosis of CSWS. In addition, previous literature has shown that normal or near‐normal outcome is rare in CSWS, and at least half of the patients remain severely impaired (Tassinari et al., 2000; Nickels & Wirrell, 2008; Loddenkemper et al., 2011; Sánchez Fernández et al., 2012c; Seegmuller et al., 2012). Although most respondents consider CSWS as a devastating epileptic encephalopathy with severe sequelae even if treated correctly, around one fourth have indicated that it did not leave sequelae if epilepsy was treated early and around one tenth suggested that cognitive problems resolved with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one third of our respondents diagnose CSWS based on EEG assessment alone and two thirds of respondents considered that regression was typical but not required for the diagnosis of CSWS. In addition, previous literature has shown that normal or near‐normal outcome is rare in CSWS, and at least half of the patients remain severely impaired (Tassinari et al., 2000; Nickels & Wirrell, 2008; Loddenkemper et al., 2011; Sánchez Fernández et al., 2012c; Seegmuller et al., 2012). Although most respondents consider CSWS as a devastating epileptic encephalopathy with severe sequelae even if treated correctly, around one fourth have indicated that it did not leave sequelae if epilepsy was treated early and around one tenth suggested that cognitive problems resolved with age.…”
Section: Discussionmentioning
confidence: 99%
“…Although most respondents consider CSWS as a devastating epileptic encephalopathy with severe sequelae even if treated correctly, around one fourth have indicated that it did not leave sequelae if epilepsy was treated early and around one tenth suggested that cognitive problems resolved with age. Based on available data, regression may be considered an integral part of the definition of CSWS, and cognitive prognosis is generally poor (Tassinari et al., 2000; Loddenkemper et al., 2011; Sánchez Fernández et al., 2012c,e; Seegmuller et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some patients present with moderate improvements after seizure freedom. However, most patients remain severely impaired [2, 3, 6, 47]. The impact of interictal spikes on neurocognitive features is a matter of debate, and it is not clear whether an increased amount of epileptiform activity is associated with a worse cognitive outcome [4, 48, 49].…”
Section: Evolution Over Timementioning
confidence: 99%
“…96,97 However, NFLE can present with RLS-like symptoms. 98 Nonconvulsive status epilepticus can present as recurrent hypersomnia. 99 Partial seizures can mimic sleep terrors.…”
Section: Less Common Clinical Presentations Of Epileptic and Nonepilementioning
confidence: 99%